MENINGKATKAN PRESTASI BELAJAR IPA DENGAN MEDIA VIDEO DAN METODE STAD SEMESTER 1 KELAS IV SDN BABADAN TAHUN 2015/2016 - -, Wuryanto (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2016)
Issues to be discussed include how to improve science learning achievement of material structureand function of plant parts in the fourth grade students of SDN Babadan Bonang District of Demakusing STAD method with the application of video media. The subjects were fourth grade students ofSDN Babadan Bonang District of Demak district by the number of students 23 students. This studyuses classroom action research design with two cycles. Each cycle consists of action planning,action, observation, and reflection. Results of preliminary tests before (prasiklus) the averagevalue reached 59.57. This value is still less so held the first cycle measures the average valueobtained was 68.70 dnn class has increased very significantly in the second cycle of 80.00